Subconjunctival injectable dendrimer-dexamethasone gel for the treatment of corneal inflammation. (May 2017) - Soiberman, Uri; Kambhampati, Siva P.; Wu, Tony; Mishra, Manoj K.; Oh, Yumin; Sharma, Rishi; Wang, Jiangxia; Al Towerki, Abdul Elah; Yiu, Samuel; Stark, Walter J.; Kannan, Rangaramanujam M.
Abstract: Corneal inflammation is often encountered as a key pathological event in many corneal diseases. Current treatments involve topical corticosteroids which require frequent instillations due to rapid tear turnover, causing side-effects such as corneal toxicity and elevated intraocular pressure (IOP). Hence, new interventions that can reduce side effects, dosing frequency, and increase patient compliance can be highly beneficial. In this study, we explore a subconjunctival injectable gel based on G4-PAMAM dendrimer and hyaluronic acid, cross-linked using thiol-ene click chemistry, incorporated with dendrimer dexamethasone (D-Dex) conjugates as a potential strategy for sustained delivery and enhanced bioavailability of corticosteroids. The efficacy of the injectable gel formulation was evaluated in a rat mild alkali burn model. Fluorescently-labelled dendrimers (D-Cy5) incorporated in the gel release D-Cy5 in vivo . The released D-Cy5 selectively targets and localizes within corneal macrophages in inflamed rat cornea but not in healthy controls. This pathology dependent biodistribution was exploited for drug delivery, by incorporating D-Dex in the injectable gel. The attenuation of corneal inflammation by D-Dex gels was assessed using various clinical and biochemical parameters over a 2-week period. Subconjunctival D-Dex gel treatment resulted in favorable clinically-relevant outcomes with reduced central corneal thickness and improved corneal clarity compared to free-Dex and placebo gel controls. The extent of corneal neovascularization was significantly reduced in the D-Dex group. These findings suggest that D-Dex attenuates corneal inflammation more effectively than free-Dex by attenuating macrophage infiltration and pro-inflammatory cytokines expression. A significant elevation in IOP was not observed in the D-Dex group but was observed in the free-Dex group. This novel injectable D-Dex gel may be a potential drug delivery platform for the treatment of many inflammatory ocular surface disorders such as dry eye, auto-immune keratitis and post-surgical complications where frequent steroid administration is required. Graphical abstract: